New Cognitive Approaches in Process-Oriented Translation Training - Lee-Jahnke, Hannelore (Meta, 2005)
AbstractAfter a brief description of the state of the art, this paper presents new methods of process-oriented translation training. The different instruments used in class, such as questionnaires and other tools, the learning outcome of these methods and the improvement of proficiency achieved by these means, constitute the core of the paper. The third and final part deals with the preliminary results of an interdisciplinary research project with the Department of Neurology of the University Hospital of Geneva, and the prospects for applying this type of research to translation training.